Trends in Tuberculosis Treatment Success Rates in East Kalimantan, Indonesia, 2021–2023 - Walpian Noranas; Wa Nuni; Wulandari; Yunita Dewi Damayanti; Zaskia Sabrina Qhalbi; Putri Feta Sweety (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis, characterized by the formation of necrotic granulomatous tissue (caseous necrosis) as an immunological response to infection. TB is primarily transmitted through airborne droplets and spreads more readily among individuals with compromised immune systems. It is estimated that one person with active TB can infect up to 10–15 individuals in close contact. The disease disproportionately affects the productive age group, thereby exerting a substantial impact on human resource quality and economic productivity. Despite ongoing control efforts, TB remains a major public health challenge globally and in Indonesia. East Kalimantan Province ranks 17th nationally and second within the Kalimantan region in terms of TB case burden. Objective: This study aims to describe the tuberculosis treatment success rate in East Kalimantan Province during the period 2021–2023. Methods: A quantitative descriptive study was conducted using secondary data obtained from the East Kalimantan Provincial Health Profile. Data were analyzed based on annual TB treatment success rates and presented in graphical form to identify temporal patterns and trends. Results: The findings indicate an improvement in TB treatment success rates in certain years between 2021 and 2023. This upward trend reflects the effectiveness of regional TB control program implementation, including case detection, treatment adherence, and monitoring mechanisms. Conclusion: The tuberculosis treatment success rate in East Kalimantan Province demonstrates a positive trend. Nevertheless, persistent challenges such as delayed diagnosis, poor treatment adherence, and limited access to healthcare services remain. Strengthening community education, enhancing healthcare service capacity, and improving early detection are essential to support TB elimination efforts in the region.